THE GLUTATHIONE DIURNAL CYCLING IN Dunaliella salina - Moh Muhaemin (JOURNAL OF COASTAL DEVELOPMENT, 2008)
Glutathione is intracellular low molecular weight thiols as detoxification agent in most marine microalgae. The short continuous culture was used to describe diurnal cycle of intracellular glutathione during light: dark period. The result showed that glutathione tend to follow light period and minimum levels at the end of dark period. Cysteine exhibited twofold diurnal variations, maximum levels at the early dark period. Those may prove that glutathione may have an important role as an antioxidant in marine phytoplankton.